2018
DOI: 10.1080/15287394.2018.1490675
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and occupational exposure assessment for Fischer-Tropsch synthetic paraffinic kerosene

Abstract: Fischer-Tropsch (FT) Synthetic Paraffinic Kerosene (SPK) jet fuel is a synthetic organic mixture intended to augment petroleum-derived JP-8 jet fuel use by the U.S. armed forces. The FT SPK testing program goal was to develop a comparative toxicity database with petroleum-derived jet fuels that may be used to calculate an occupational exposure limit (OEL). Toxicity investigations included the dermal irritation test (FT vs. JP-8 vs. 50:50 blend), 2 in vitro genotoxicity tests, acute inhalation study, short-term… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Moreover, while not strictly genotoxic, studies showed definitive cellular toxicity when blood plasma was exposed to JP-8 in laboratory tests, instances of premature death, increased malignancy risks and behavioral disturbances, nervous system effects, and a 2- to 5-fold increase in the risk of hearing loss . Additionally, occupational exposure to JP-8 was associated with an increased incidence of miscarriages in female military aircraft personnel; however, the literature review conducted by the particular authors did not reach definitive conclusions regarding the relationship between exposure to aviation fuels or specific constituents and adverse reproductive health outcomes.…”
Section: Toxicitymentioning
confidence: 97%
See 4 more Smart Citations
“…Moreover, while not strictly genotoxic, studies showed definitive cellular toxicity when blood plasma was exposed to JP-8 in laboratory tests, instances of premature death, increased malignancy risks and behavioral disturbances, nervous system effects, and a 2- to 5-fold increase in the risk of hearing loss . Additionally, occupational exposure to JP-8 was associated with an increased incidence of miscarriages in female military aircraft personnel; however, the literature review conducted by the particular authors did not reach definitive conclusions regarding the relationship between exposure to aviation fuels or specific constituents and adverse reproductive health outcomes.…”
Section: Toxicitymentioning
confidence: 97%
“…Naphthalene or bicyclic aromatics produce increased soot, smoke, and thermal radiation, making them also less desirable for aviation fuel usage, and desulfurized or ultralow sulfur diesel fuel has now become a requirement under regulations as a means to minimize corrosion on turbine metal parts . However, although it was claimed that biofuels might be genotoxic, most adverse health effects of alternative fuels were the same if not slightly better compared to the toxicological profile of JP-8 and Jet A-1. ,,,, Below, we discuss a few available studies on the toxicity of alternative fuels and comparisons with conventional aviation fuels.…”
Section: Toxicitymentioning
confidence: 99%
See 3 more Smart Citations